An integrated quantitative framework to support design of resilient alternatives to manage urban flood risks. (13th December 2018) - Miguez, Marcelo G.; Raupp, Igor P.; Veról, Aline P.
Abstract : Urban floods can disrupt city services and cause significant damage. This study intends to contribute to the flood control discussion by proposing a design framework combining flood risk, resilience, and economic feasibility to support decision‐making among flood control alternatives. First, a hydrodynamic model (Urban Flood Cell Model‐MODCEL) simulates flood maps for different return periods. Then, a multicriteria flood risk index is used to introduce socioeconomic variables and an integrated flood resilience index indicates the best alternative for maintaining risks at an acceptable level under future pressures, that is, guaranteeing that future risks will not increase significantly. Finally, economic feasibility is assessed, adding a benefit–cost analysis, considering the expected avoided losses over a given time. To illustrate this discussion, two design alternatives are compared for a project lifetime of 50 years in the Dona Eugenia watershed, in the metropolitan area of Rio de Janeiro, Brazil. The proposed framework showed that the most complete (and initially preferred) alternative, which considered a whole set of distributed sustainable urban drainage and river restoration measures, was not economically feasible. A variant of this alternative focusing on fluvial floodable parks and river restoration, avoiding individual adaptations (like implementing green roofs in existing buildings), showed more sustainable results.